Justice for kids : keeping kids out of the juvenile justice system - Dowd, Nancy E., 1949- (New York : New York University Press, 2016)
Children and youth become involved with the juvenile justice system at a significant rate. While some children move just as quickly out of the system and go on to live productive lives as adults, other children become enmeshed in the system, developing deeper problems and or transferring into the adult criminal justice system. This book focuses on ways to intervene at the earliest possible point to rehabilitate and redirect-to keep kids out of the system-rather than to punish and drive kids deeper. It presents a compelling argument for rethinking and restructuring the juvenile justice system as we know it. The book explores the system's fault lines with respect to all children, and focuses in particular on issues of race, gender, and sexual orientation that skew the system.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Juvenile justice, Administration of -- United States; Pre-trial intervention -- United States; Restorative justice -- United States; Juvenile delinquency -- United States -- Prevention; True Crime; United States of America, USA; Age groups: adolescents; Social services & welfare, criminology; Juvenile offenders; Criminal law: procedure & offences